FORMATION DIAGNOSTICS OF EDUCATIONAL ACHIEVEMENTS AND ROLE OF THE SYSTEM-ACTIVITY APPROACH IN IMPROVING THE QUALITY OF GEOGRAPHICAL KNOWLEDGE OF STUDENTS - Kumarbekuly, Sanat; Abdimanapov, Bakhadurkhan (Pedagogy and Psychology, 2022)
The article discusses the role and methodology of diagnostics of previously formed educational achievements of students, which are necessary for further coordination of educational activities to achieve the educational goals. On the example of the 8th and 9th grade’s geography material content, the experience of conducting experimental work with students on the diagnosis of acquired knowledge and the formation of new educational results is shown. Modernization of Kazakhstan's school education has undergone significant transformations in recent years. The adoption of new educational standards of teaching by educational institutions and its understanding by the teaching staff is aimed at solving a number of tasks, the main task of which is the formation of a new Kazakh personality of a student who will be able to independently organize his/her further trajectory and will navigate in the modern information environment without difficulty. Therefore, the most important aspect of the students’ activities of general education institutions is their functional literacy, information, and communication competence. It is important to note that in the formation of these competencies, and in solving problems in the formation of skills and organization of independent work, which is aimed at obtaining various information, for the qualitative solution of educational tasks, clear criteria and methods of measuring educational achievements are needed. In our opinion, one of the most effective pedagogical and didactic technologies of knowledge formation is the system-activity approach. In this aspect, sections of geography such as physical geography, social and economic geography have versatile and most successful opportunities for activating educational activities. The modern strategy of Kazakhstan education focuses teachers on the formation of students' subject competencies, which are based on comprehensive knowledge; practical skills and abilities; creative and activity approach; and personal responsibility. The main emphasis in the school education system of the XXI century is directed on the intellectual and moral development of the individual, which implies the need for the formation of critical thinking, the ability to navigate in the modern information space.